The Acute Effects of Motor Imagery Combined With Action Observation Breathing Exercise on Cardiorespiratory Responses, Brain Activity, and Cognition: A Randomized, Controlled Trial - Ebrar Atak; Amine Ataç (Cardiovascular Therapeutics)
Trial Registration: ClinicalTrials.gov identifier: NCT06099483